Strategies for qualitative secretarial services in the Nigerian labour market - Omeje, Leticia O.; Ogbuke, Elizabeth (Journal of Professional Secretaries and Office Administrators, 2015)
This write-up tries to reveal that the demand/need for employment of confidential secretaries is drastically declining in the labour market. Gone are the days when every establishment, no matter how small sought the services of professional secretaries. This is due to the introduction of computer and accessories in the country where every Dick and Harry who has the least experience in computer claims to have the capability of rendering secretarial services. This notion has even affected the number of students going in for the course. It has also affected the number of institutions offering the course in addition to forcing some institutions to change the course name to ’Information Technology’, `Office Management’, etc. The paper also tries to enumerate the similarities and differences between a Professional Confidential Secretary and Computer Operator. In addition to the duties of a confidential secretary, it goes further to explain that although there is a distinct difference between a professional Secretary and a computer operator in the services being rendered, for the professional secretary to thrive well in the Nigerian labour market, there is need to strategize and tremendously improve the quality of services being rendered by the professional secretary. The write-up also goes on to outline some of the major areas to be strategized such as enhanced service delivery, innovations, display of professionalism, self development/enhancement, etc. Conclusively, the writer believe that with concrete strategized qualitative services, instead of going into extinction, the sky would be the limit of our professional secretaries in the Nigerian labour market.